1999
DOI: 10.1007/s004210050585
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to light isometric and aerobic exercise in 21- and 59-year-old males

Abstract: The effects of aging on the cardiovascular response to continuous light isometric and aerobic exercise remains to be determined. Thus, the purpose of this study was to compare the cardiovascular response of young and older males during light handgrip and cycle ergometry exercise. Blood pressure, heart rate, rate pressure product, as well as pre-ejection period (derived from impedance cardiography) were obtained for 15 young [mean (SE) age: 21 (0.7) years] and 15 older males [59 (0.8) years] during and after li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…These findings are age dependent because the two major autoregulation activating factors (BP changes and pCO 2 ) did not differ in both investigated groups. However, it must be mentioned that the heart rate in both groups differed in common with other ergometer exercise studies in healthy elderly subjects [25]. Presumably, the sympathetic influence is less pronounced in the older group, but the cardiovascular system is under greater haemodynamic stress [25].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are age dependent because the two major autoregulation activating factors (BP changes and pCO 2 ) did not differ in both investigated groups. However, it must be mentioned that the heart rate in both groups differed in common with other ergometer exercise studies in healthy elderly subjects [25]. Presumably, the sympathetic influence is less pronounced in the older group, but the cardiovascular system is under greater haemodynamic stress [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo em trabalho intenso, a FC não costuma ultrapassar 70% da FC máx, o que tende a induzir um duplo-produto de baixo risco cardíaco (14,27,40). Entre as adaptações crónicas mais importantes decorrentes da práti-ca regular de exercícios de força, podem ser mencionadas a possível redução da FC (30) e da PA de repouso (41) e, principalmente, a menor sobrecarga cardíaca durante o exercício, com menor DP associado (10,46,48,50). Por estas razões, acumulam-se os pareceres e recomendações em que o treinamento da força é indicado para indivíduos com ou sem doença cardiovascular.…”
Section: Considerações Finais E Conclusãounclassified
“…Understanding the pressor response during dynamic resistance exercise using large muscle groups is essential for exercise prescription. However, most previous studies have focused on static resistance exercise (11,12,16,33), and have provided little information regarding the cardiovascular response during dynamic resistance exercise (10), or the interaction between age and BP response to dynamic resistance exercise using large muscle groups. We found that pressor responses during dynamic resistance exercise at relative intensities were lower in middle-aged than in young men, suggesting that the BP response to dynamic resistance exercise may be attenuated with advancing age despite age-associated arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%